Effects of a Yoga-Based Intervention on Self-Compassion, Depression and Loneliness in Obese Adolescents - Erdoğan, Ramazan; Shafaei, Hassan (International Journal of Sport Studies for Health, 2025)
Objective: The aim of this study was to examine the effects of a yoga-based intervention on self-compassion, depression and loneliness in obese adolescents. Methods and Materials: A quasi-experimental design with a pretest-posttest framework was utilized in this research, which involved a sample of 58 male adolescents aged 15 to 17 who were classified as obese. The participants were split into two equal groups: an intervention group of 29 individuals who participated in an eight-week yoga program, and a control group of the same size. To evaluate the research variables, The Self-Compassion Scale, The Patient Health Questionnaire, and The DJGLS-6 were employed, and the data were subsequently analyzed using ANCOVA. Findings: The analysis conducted at the conclusion of the intervention revealed significant differences among all groups regarding these parameters (P<0.001). These results indicate that the yoga intervention effectively improved self-compassion while simultaneously decreasing levels of depression and loneliness in obese male adolescents. Conclusion: Yoga can be regarded as a valuable complementary strategy for alleviating certain psychological disorders in obese male adolescents. Given that young individuals typically enjoy engaging in physical activities like yoga, their participation can lead to significant benefits.